Observation of the bulk ion density peaking in a discharge with an impurity hole in the LHD. (7th June 2017) - Perek, A.; Ida, K.; Yoshinuma, M.; Goto, M.; Nakamura, Y.; Emoto, M.; Jaspers, R.
Abstract: Radial profiles of bulk ion and impurity ions density are simultaneously measured and quantified using charge exchange spectroscopy and peaking parameter, C v . The peaking parameter is positive for inward and negative for outward convection in a plasma with an impurity hole in the Large Helical Device. Following the formation of an impurity hole associated with the transition from L-mode to ion ITB plasma, the bulk ion becomes peaked by the inward convection ( C v > 0 ), while impurities (helium and carbon) become hollow due to the outward convection ( C v < 0 ) . In contrast to the ion ITB plasma, in the L-mode plasma the impurity profiles are peaked ( C v > 0 ), where the bulk ion density profile remains flat ( C v ∼ 0 ) . Understanding of the impurity behavior in the ion ITB plasma could lead to a self cleaning plasma reactor concept, with an efficient impurity exhaust.